A review of the conservation status of Black Stork Ciconia nigra in South Africa, Lesotho, and Eswatini. (11th April 2023) - Lee, Alan Tristram Kenneth; Whitecross, Melissa A.; Smit-Robinson, Hanneline A.; Allan, David G.; van den Heever, Linda; Jenkins, Andrew; Retief, Ernst F.; Colyn, Robin B.; Tarboton, Warwick; Chetty, Kishaylin; Brink, Christiaan Willem
Summary: Across South Africa, Lesotho, and Eswatini, long-term citizen science atlas data have suggested concerning declines in the population of Black Stork Ciconia nigra. Unlike the Asian and European populations, the southern African Black Stork population is described as resident and is listed as "Vulnerable" in South Africa, Lesotho, and Eswatini. Here we report on surveys of historical nesting locations across northern South Africa, finding evidence for nest site abandonment and limited evidence of recent breeding. We undertook detailed species distribution modelling within a maximum entropy framework, using occurrence records from the BirdLasser mobile app. We cross-validated the models against information in the Southern African Bird Atlas Project (SABAP2) database, highlighting Lesotho as an important potential breeding area. Additionally, we used SABAP2 to assess population trends by investigating interannual patterns in reporting rate. Comparing current reporting rates with those from SABAP1 (1987–1992), we found that there has been a dramatic decrease. We noted that a large proportion of the population occurs outside the breeding range during the breeding season, suggesting a considerable non-breeding population, especially in the extensive wildlife refuge of the Kruger National Park. The slow declines observed might be indicative of a population which is not losing many adults but is failing to recruit significant numbers of juveniles due to limited breeding. Using densities derived from transect surveys, we used predictive models to derive estimates of breeding range carrying capacity and a population estimate, which suggested declines to numbers around 600 for this subregion. Minimising disturbance at breeding sites of this cliff-nesting species and improving water quality at key population strongholds are pathways to improving the status of the species in the subregion.